2009
DOI: 10.1007/s11274-009-0155-7
|View full text |Cite
|
Sign up to set email alerts
|

Application of thymol and iprodione to control garlic white rot (Sclerotium cepivorum) and its effect on soil microbial communities

Abstract: The effect of different dosages of thymol alone, iprodione alone and combinations of thymol and iprodione on white rot disease of garlic and its impact on soil microbial community structure were investigated under greenhouse conditions. Thymol alone or in combination with the fungicide iprodione did not appear to reduce either white rot incidence or soil sclerotia density as compared to an infected control. However, iprodione alone or in combination with thymol reduced soil fungal biomass. In addition, iprodio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Iprodione (3-(3,5-dichlorophenyl)-Nisopropyl-2,4-dioxoimidazolidine-1-carboxamide), a contact dicarboximide fungicide widely used in a variety of crops, inhibits glycerol synthesis and hyphal development by cutting off signal transduction [43], as does fludioxonil. Iprodione can modify the structure of the soil bacterial community, as reported in a recent research [24]. Interference with signal transduction by dicarboximide fungicide vinclozolin ((RS)-3-(3,5-dichlorophenyl)-5-methyl-5-vinyl-1,3-oxazolidine-2,4-dione) caused low growth rate, abnormality, and changes in the productions of hexoses and chitin in treated B. cinerea [46].…”
Section: Effects On Signal Transductionmentioning
confidence: 54%
“…Iprodione (3-(3,5-dichlorophenyl)-Nisopropyl-2,4-dioxoimidazolidine-1-carboxamide), a contact dicarboximide fungicide widely used in a variety of crops, inhibits glycerol synthesis and hyphal development by cutting off signal transduction [43], as does fludioxonil. Iprodione can modify the structure of the soil bacterial community, as reported in a recent research [24]. Interference with signal transduction by dicarboximide fungicide vinclozolin ((RS)-3-(3,5-dichlorophenyl)-5-methyl-5-vinyl-1,3-oxazolidine-2,4-dione) caused low growth rate, abnormality, and changes in the productions of hexoses and chitin in treated B. cinerea [46].…”
Section: Effects On Signal Transductionmentioning
confidence: 54%
“…This risk could be minimized by the use of thymol. Miñambres et al (2010) evaluated the in vitro impact of different thymol doses on the microbial communities in the soil, when applied alone or in combination with a fungicide, and observed that the use of thymol did not significantly alter the microbial activity and biomass, and only posed a risk to the survival of gram-negative bacteria. However, the application of the fungicide in the soil caused a greater reduction in the microbial activity and fungal biomass than thymol.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of bioactivity, however, is determined by the substituent present (Miñambres et al . ; Dambolena et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Natural phenols such as carvacrol, thymol, eugenol and isoeugenol have been shown to possess a wide range of bioactivities. These include the antioxidant properties (Dambolena et al 2010), radical scavengers (Bortolomeazzi et al 2010), antimicrobial (Miñambres et al 2010), including antifungal (Voda et al 2004;Dambolena et al 2011) or antitoxicogenic activity, have been reported (Dambolena et al 2012). Several reports attribute the antimicrobial activity of essential oils from aromatic plants to the terpenoid and phenolic compounds present in them (Oliva et al 2013).…”
mentioning
confidence: 99%